Sleep and adolescence: How many hours sleep teenagers need? Sono e adolescência: Quantas horas os adolescentes precisam dormir? - Pereira E.F.* (2015)
© 2015, Editora Cientifica Nacional Ltda. All Rights Reserved.Objective: Determine specificity and sensibility, to point the best cut of for the sleep duration as predictor of excessive daytime somnolence in adolescents. Methods: One thousand three hundred ffty-nine adolescents aged 14 to 21 years of two cities from South Brazil answered a questionnaire about sleep habits and daytime somnolence. To estimate the predictive capacity of sleep duration for the excessive daytime somnolence was used the Receiver Operating Characteristic. Results: The sleep duration mean for adolescents with excessive daytime somnolence was 7.9 hours and for those without excessive daytime somnolence was 8.33 hours (p < 0,001). The prevalence of excessive daytime somnolence was 35.7%. Significant and negative correlation between the sleep duration and the ages analyzed was observed (p < 0,001). The Receiver Operating Characteristic analysis indicated a minimum duration of 8.33 hours as protection for excessive daytime somnolence. Conclusion: High prevalence of excessive daytime somnolence was observed and is proposed as a possible sleep duration a minimum of 8.33 hours of sleep in the days with classes for adolescents to avoid this outcome.